An Electronic Platform for the Integrated Monitoring of Technical and Economic Data of Farms - Anna Tafidou; Asimina Kouriati; Evgenia Lialia; Angelos Prentzas; Eleni Dimitriadou; Kyriaki Tafidou; Thomas Bournaris (Proceedings, 2024)
The digitalization of farming is considered the fourth revolution in agriculture. The necessity of providing decision support tools and electronic platforms to help Greek farmers in their work is becoming increasingly evident. For this reason, this article presents the electronic platform called “FarmEconomicMonitoring” to monitor the operations of farms to control production costs and improve efficiency. With the use of the electronic platform by the farmer–entrepreneurs, their easy adaptation to the new technologies concerning decision-making and farm management systems becomes achieved.